Association between Parental Feeding Styles and Excess Weight, and Its Mediation by Diet, in Costa Rican Adolescents - Mendoza Herrera, Kenny (2022)
Background. Whereas parental feeding styles (PFS) influence children’s diet, less is known about this relationship in adolescents. Methods. A cross-sectional study in 686 Costa Rican adolescents (13–18 years) evaluated 4 validated PFS scores: healthy eating verbal encouragement; scolding; directly controlling diet; instrumental/emotional. Diet was evaluated through 3-day food records, deriving a Traditional Costa Rica Adolescents Diet Score (TCRAD). Excess weight (EW) measured by BMI was dichotomized following standards. Regression-based mediation analysis estimated the overall and sex-stratified odds ratios of EW for natural direct (NDE), natural indirect (NIE), and total effects (TE) of the pathway PFS-TCRAD-EW. Results. A one-unit increase in the direct control PFS score was associated with higher EW odds overall [(TE: 1.55; 95% CI: 1.04–2.31; p-value = 0.033), (NDE: 1.52; 95% CI: 1.02–2.27; p-value = 0.039)], and in boys [(TE: 2.13; 95% CI: 1.04–4.38; p-value = 0.039), (NDE: 2.10; 95% CI: 1.03–4.31; p-value = 0.042)]. Nonsignificant mediation by TCRAD was observed for the healthy eating verbal encouragement PFS overall (p-value = 0.06). Associations for the instrumental/emotional and scolding PFS were not significant. Conclusions. Direct diet control from parents may contribute to adolescents’ excess weight, particularly among boys. Parents encouraging healthy eating might support adolescents’ healthy weight through a healthy diet. Longitudinal research should clarify the association between PFS and diet-related outcomes among diverse adolescents.